Presença tecnológica na comunicação intergeracional e na qualidade de vida de idosos indígenas - Silva, Carine Alves da (2011)
Longevity is a world phenomenon that generates challenges for society, since it implies in its social, economic, educational and health demand. This reality is not the same for the indigenous population, thus the elderly find greater difficulties with relation to the non-indigenous, since they live in distant places and have many difficulties of access to resources for its survival. It is observed the concern of protecting entities in providing subsides for teams that work in the villages. Therefore, technology may provide communication and the intergenerational relationship of indigenous, and their costumes may be followed by their descendent, besides spreading caingangues culture to the world. The objective of this transversal qualitative quantitative study was to know about the technological presence in the intergenerational process and life quality of indigenous elderly residents in Bananeira village, in the city of Gramado dos Loureiros RS. The sample was intentional; the leader of the village, elderly, who were 60 or more than 60 years old, and children studying in the fourth year of school, and health professionals who work in the village participated in this research. The data were collected by means of semi-structured questionnaires, elaborated in order to collect information on communication processes and generational interaction, the use of technologies and communicative spaces, as well as on the indigenous life quality and elderly health. Descriptive statistics was used to describe variables of quantitative character; but the ones of qualitative character were systematized in different categories of analysis. The high index of (70%) of elderly seemed to have some kind of health problem; and their majority use their free time to listen to the radio, visit some friends and relatives; therefore, the access to technology improved the quality of life of them and the others who live in the village